2018
DOI: 10.1111/aec.12629
|View full text |Cite
|
Sign up to set email alerts
|

Red‐backed fairywrens adjust habitat use in response to dry season fires

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In only five species (16%) were the direct impacts of fire on mortality assessed in multiple studies (Figure 5). Across all studies, there was an enormous range in the body sizes of the animal species studied, from 7.9 g red‐backed fairy‐wrens ( Malurus melanocephalus ) (Murphy et al, 2010; Sommer et al, 2018) to the world's largest terrestrial animal—the 4400 kg African bush elephant ( Loxodonta africana ) (Woolley et al, 2008). Most studies investigated the direct effects of fire on the mortality of animals that are currently listed as Least Concern according to the IUCN Red List of Threatened Species (74% of species; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In only five species (16%) were the direct impacts of fire on mortality assessed in multiple studies (Figure 5). Across all studies, there was an enormous range in the body sizes of the animal species studied, from 7.9 g red‐backed fairy‐wrens ( Malurus melanocephalus ) (Murphy et al, 2010; Sommer et al, 2018) to the world's largest terrestrial animal—the 4400 kg African bush elephant ( Loxodonta africana ) (Woolley et al, 2008). Most studies investigated the direct effects of fire on the mortality of animals that are currently listed as Least Concern according to the IUCN Red List of Threatened Species (74% of species; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For example, sampling immediately before and after the first early-season fires at the Territory Wildlife Park revealed no change in the abundance or composition of skink species (Figure 3), and early-season fires caused no direct mortality of frill-necked lizards (Chlamydosaurus kingii) at Kapalga (Griffiths & Christian, 1996). Even high-intensity fires may cause no direct mortality, such is the case for red-backed fairy wrens (Malurus melanocephalus) (Murphy et al, 2010;Sommer et al, 2018) and small rodents (Leahy et al, 2015) in the Kimberley. However, late-season fires at Kapalga caused 30% mortality in frill-necked lizards (Griffiths & Christian, 1996), and my unpublished observations of insects climbing up trees in response to smoke from experimental fires at the Territory Wildlife Park (cf.…”
Section: Insight 2 the Main Effects Of Fire On Fauna Are Indirect mentioning
confidence: 99%
“…Such effects can occur after individual fires due to loss of ground-layer vegetation and associated resources. For example, although fire causes no direct mortality of red-backed fairy wrens, it leads to changes in habitat use (Sommer et al, 2018) and reproductive success (Murphy et al, 2010). Experimental fires at the Territory Wildlife Park led to higher rates of myrmecochorous seed collection and dispersal by ants in the months after burning due to increased foraging distances following simplification of ground-layer habitat (Parr et al, 2007).…”
Section: Insight 2 the Main Effects Of Fire On Fauna Are Indirect mentioning
confidence: 99%
“…Australian tropical savannas are characterized by a history of frequent wildfires, but many species inhabiting these areas are in decline and are negatively-affected by fire (Franklin et al 2005, Woinarski andLegge 2013). Previous studies of red-backed fairywrens in this context have shown that wildfires lead to decreased reproductive output (Murphy et al 2010), increased social connectivity and shifting habitat use (Sommer et al 2018) in this species. Although our study did not focus on these characteristics, our observations of red-backed fairywrens support these findings as wildfires forced individuals to leave breeding territories and flock in unusual numbers in the few remaining unburned areas at both study sites (Boersma, pers.…”
Section: Discussionmentioning
confidence: 98%